Frequency of BRCA1 and BRCA2 causative founder variants in ovarian cancer patients in South-East Poland - Tomasz Kluz; Andrzej Jasiewicz; Elżbieta Marczyk; Robert Jach; Anna Jakubowska; Jan Lubiński; Steven A. Narod; Jacek Gronwald (Hereditary Cancer in Clinical Practice, 2018)
Abstract Background Causative variants in BRCA1 and BRCA2 are well-established risk factors for breast and ovarian cancer. In Poland, the causative founder variants in the BRCA1 are responsible for a significant proportion of ovarian cancer cases, however, regional differences in the frequencies of various mutations may exist. The spectrum and frequency of BRCA1/2 mutations between ovarian cancer patients have not yet been studied in the region of South-East Poland. Methods We examined 158 consecutive unselected cases of ovarian cancer patients from the region of Podkarpacie. We studied 13 Polish causative founder variants in BRCA1 (c.5266dupC, c.4035delA, c.5251C > T, c.181 T > G, c.676delT, c.68_69delAG, c.3700_3704delGTAAA, c.1687C > T, c.3756_3759delGTCT) and in BRCA2 (c.658_659delGT, c.7910_7914delCCTTT, c.3847_3848delGT, c.5946delT). Results A BRCA1 causative founder variants were detected in 10 of the 158 (6.3%) ovarian cancer cases. BRCA2 causative founder variants were not observed. The c.5266dupC mutation was detected in 6 patients, c.181 T > G mutation in 3 patients and the c.676delT mutation in 1 patient. The median age of diagnosis of the 10 hereditary ovarian cancers was 55.5 years of age. Conclusions The frequency of 13 causative founder variants in Podkarpacie was lower than in other regions of Poland. Testing of three BRCA1 mutations (c.5266dupC, c.181 T > G, c.676delT) should be considered a sensitive test panel.